Educational conversation circles with pregnant women in the scope of primary care: An experience report (Research, Society and Development, 2022)
Introduction: The use of educational practices aimed at sensitizing health users in the scope of primary care acts as a tool that helps to preserve the health of these individuals. This article aims to report the experience of Medical Students and describe the execution of an educational activity aimed at promoting health and raising awareness about healthy eating practices aimed at pregnant women using the services of a Basic Health Unit (BHU). Methodology: based on conversation circles involving 45 pregnant women, the activity being performed four times during the first semester of 2022, through the use of graphic material and a playful educational folder, on the main undesirable symptoms of the first trimester of pregnancy, elucidating nutritional guidelines to mitigate or avoid them. Results and Discussion: the lived experience enabled the development of skills and the improvement of the perception of social commitment in the collective construction of the Academicians' citizenship. The development of prevention and health promotion actions, through practices in humanized food and nutrition education, favored the increase of the bond between future health professionals and pregnant users of the health services provided at the UBS. Conclusion: The development of the activity provided the Medical Students with a unique opportunity for practical learning, something that ended up contributing significantly to the training and development of students' skills, regarding the execution and promotion of health promotion in the scope of care primary health.